Plasma Enhanced Ionic Liquid Catalysis for the Production of Biodiesel from Chicken Skin - Elsheikh, Yasir Ali; Hudha, Khisbullah; Al Mahri, Hamad; Al Mamari, Asma (Automotive Experiences, 2025)
Biodiesel production has emerged as a promising area of alternative fuel development, though challenges remain in sourcing cost-effective raw materials and selecting effective catalysts. This study investigates the production of biodiesel from chicken skin fat using two distinct catalytic methods. In the first method, transesterification was catalyzed by trioctyl ammonium hydrogen sulfate (Oct3AMHSO4) at concentrations ranging from 3-6 wt%. In the second method, the same catalyst was combined with plasma to enhance the reaction. The first method yielded only 35% biodiesel with 3.5 wt% Oct3AMHSO4, while the second method, under identical conditions, showed a significant improvement, achieving a 97.4% yield. The impact of temperature variations (40-80°C) was also explored with different catalyst concentrations (3-6 wt%). Increasing the catalyst concentration to 3.5% and raising the temperature to 55°C resulted in a notable yield improvement. However, further increases in temperature or catalyst concentration beyond 3.5% led to a decline in yield, particularly at temperatures exceeding 60°C. This suggests that certain reaction conditions may reverse the transesterification process, pushing the products back toward the reactants and reducing efficiency.